Efficiency of laser versus bur in impacted mandibular third molar surgery: An original research - Niladri Maiti; Piyush Sharma; Samiksha Singh Jadon; Fida Qadri; V R Chandra Babu Pamidi; Sagar Ramesh Ganvir; Rahul V C Tiwari (Wolters Kluwer Medknow Publications, 2021)
Introduction: In oral and maxillofacial surgery, their clinical application has largely been restricted to soft tissue. Hence, the aim of this study was to assess the feasibility of erbium-yttrium aluminum garnet (Er: YAG) laser in bone cutting for removal of impacted lower third molar teeth and to compare its outcomes with that of surgical bur. Materials and Methods: The study comprised forty subjects requiring removal of impacted mandibular third molar, randomly categorized into two equal groups of 20 each, who had their impacted third molar removed either using Er: YAG laser or surgical bur as per their group, using standard methodology of extraction of impacted teeth. Clinical parameters such as pain, bleeding, time taken for bone cutting, postoperative swelling, trismus, wound healing, and complications were compared for both groups. Results: Clinical parameters such as pain, bleeding, and swelling were lower in laser group than bur group, although the difference was statistically not significant. However, postoperative swelling showed a significant difference in the two groups. Laser group required almost double the time taken for bone cutting with bur. Trismus persisted for a longer period in laser group. Wound healing and complications were assessed clinically and there was no significant difference in both the groups. Conclusion: Based on the results of our study, the possibility of bone cutting using lasers is pursued, the osteotomy is easily performed, and the technique is better suited to minimally invasive surgical procedures. The use of Er: YAG laser may be considered an alternative tool to surgical bur, especially in anxious patients.